A Clinical Study on the Effect of Virechana Karma with Gandharvahastadi Kwath in the Management of Amavata w.s.r to Rheumatoid Arthritis (AYUSHDHARA, 2025)
Purpose: Amavata, which resembles rheumatoid arthritis, affects communities. Ayurveda is being considered as a treatment for Amavata because conventional medicine often fails. This study examines Gandharvhastadi Kwatha's management of Amavata. Amavata is a difficult situation (Krichra Sadhya Vyadhi) induced by Vata vitiation, Agni Vaishamya, and toxin accumulation. Madhavakara called it "Sa kashtah sarva roganam," signifying its ferocity. Amavata is mostly an Ama-related illness, hence its treatment involves detoxification. Virechana (purgation therapy) and Gandharvhastadi Kwatha are tested for treating Amavata (RA). Methods: Open-label, randomized preliminary clinical study. Patients with classical Amavata symptoms and meeting inclusion and exclusion criteria were selected from G.A.C.H, Patna's OPD and IPD. The study involved 40 patients in two phases: Amavata assessment criteria creation and validation and clinical evaluation. The assessment instrument had patient-reported symptom scores. To verify reliability and validity, randomly chosen RA/Amavata patients' data was statistically analyzed. Results: Virechana and Gandharvhastadi Kwatha improved various clinical indicators. Statistically substantial improvement was seen in morning stiffness (83.02%), swelling (81.67%), excessive thirst (56%), loss of appetite (80.00%), body heaviness (85.37%), and indigestion (81.39%). Patients experienced significant anti-inflammatory and pain-relieving benefits and functional gains. Conclusion- RA is an autoimmune condition, thus standard treatments include immunosuppressants like NSAIDs and corticosteroids, which relieve symptoms but have serious adverse effects. Modern RA treatment is inconsistent and unsafe. However, Gandharvhastadi Kwatha, along with Virechana cleansing and Samshamana Chikitsa (palliative treatment), is safer and more successful. This complete Ayurvedic treatment for Amavata reduces risks and improves outcomes.